GROWTH AND YIELD RESPONSE OF MASHBEAN GENOTYPES TO VARIOUS PLANTING DENSITIES - Khan, Muhammad Bismillah; Asif, Muhammad (Journal of Research (Science), 2001)
Response of ten mashbean genotypes namely 9010, 98-CM-525, 98-CM-524, 9006, ES-1, 9081, 98-CM-523, Mash-3, 9092 and 98-CM-522 to three planting densities viz. 10, 15 and 20 cm. was studied under field conditions during Kharif 2001. The genotype ES-1 gave significantly the highest seed yield of all other genotypes. Various planting densities significantly affected the number of branches plant-1,seed yield (kg ha-1), biomass (kg ha-1) and harvest index (%)